The influence of the implementation of corporate social responsibility (csr) on the financial performance of Indonesian banks - Grescela Nova Natalia (Institute of Accounting Research and Novation (IARN), 2022)
Nowadays, Corporate Social Responsibility (CSR) has drawn the attention of the international community (not only from developed countries but also from developing countries). This is shown by many attempts to implement a sustainable CSR concept at international level, with good responses from developing countries. This is related to problems such as global warming, depletion of the ozone layer, and pollution that threatens the sustainability of society and the environment and eventually dangers the perpetuation of human life. Hence, it is appropriate for companies to have social responsibilities. But, unfortunately, to implement CSR in a company needs a high cost. This has become one of the obstacles for a company management that has tended only to pay attention to their financial performance to adopt CSR in their business strategy. The purpose of this research is to gather an empirical evidence of CSR influence in Indonesia BUMN's bank 2001-2008's at company financial performance which is measured by Return On Equity (ROE). The data used is the allocation of CSR costs at BUMN's banks in Indonesia and the calculation of the ROE ratio for the period of year 2001 to 2008, what is got from the financial statements of each bank. Analysis with simple regressions shows that CSR has a significant effect on ROE